IMPLEMENTASI UNDANG-UNDANG NOMOR 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK TERHADAP KASUS PERDAGANGAN ANAK DI WILAYAH HUKUM POLDA BALI - Yudha Wedantara, Gede; Astiti, T. I. P. (Kertha Wicara : Journal Ilmu Hukum; Vol. 01, No. 05, November 2013, 2013)
The protection of children's rights as a victim of child trafficking should be more attention, which means that there needs to be special attention, consideration, and care and special commission of special protection for children. Based on these conditions, it is necessary to know how the implementation of child protection laws against child trafficking criminal cases. The method used is the juridical methods empirically examine how the law works in society. So later, the implementation of the law against the occurrence of a case can be seen.
Keywords: Victim, Protection and Children Right